What is the relationship between diversity and species diversity from the local to the regional scale? - Martins, Inês Isabel Santos, 1988- (2011)
Tese de mestrado. Biologia (Ecologia e Gestão Ambiental). Universidade de Lisboa, Faculdade de Ciências, 2011